On the Solvency of Nations : Are Global Imbalances Consistent with Intertemporal Budget Constraints? - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2010)
Theory predicts that a nation's stochastic intertemporal budget constraint is satisfied if net exports (NX) and net foreign assets (NFA) satisfy an error-correction specification with a residual integrated of any finite order. We test this hypothesis using data for 21 industrial and 29 emerging economies for the 1970-2004 period to search for existence of negative relationship between NX and NFA. The results show that, despite the large global imbalances of recent years, NX and NFA positions are consistent with external solvency. Pooled Mean Group error-correction estimation yields evidence of a statistically significant, negative response of the NX-GDP ratio to the NFA-GDP ratio that is largely homogeneous across countries.